Search for reality : a study of the relationship of the transcendent and the immanent as explored in poems of Wordsworth, Coleridge, Tennyson and Hopkins - Swarts, Helena Maryna (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1975.